2000
DOI: 10.1200/jco.2000.18.6.1309
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of ACVBP and m-BACOD in the Treatment of Patients With Low-Risk Aggressive Lymphoma: The LNH87-1 Study

Abstract: In this population of patients with low-risk aggressive lymphoma, toxicities of the regimens are different, but the rates of response and survival are identical. The survival advantage of ACVBP over standard regimen in patients with advanced disease is suggested by this analysis but remains to be assessed in prospective studies specifically designed for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…This justifies a close monitoring of patients treated with ACVBP in the early phase of the treatment, especially those with an initial poor performance status or those older than 65 years of age. As toxicity is strongly reduced in patients younger than 60 years of age, [9][10][11][12] it is reasonable to assume that the advantage of ACVBP over standard CHOP should be confirmed in this population.…”
Section: Acvbp Vs Chop For Poor-prognosis Aggressive Nhl 4287mentioning
confidence: 99%
See 1 more Smart Citation
“…This justifies a close monitoring of patients treated with ACVBP in the early phase of the treatment, especially those with an initial poor performance status or those older than 65 years of age. As toxicity is strongly reduced in patients younger than 60 years of age, [9][10][11][12] it is reasonable to assume that the advantage of ACVBP over standard CHOP should be confirmed in this population.…”
Section: Acvbp Vs Chop For Poor-prognosis Aggressive Nhl 4287mentioning
confidence: 99%
“…9,10 In a previous study, the comparison of this regimen with m-BACOD (cyclophosphamide, doxorubicin, vincristine, bleomycin, methotrexate, and dexamethasone), a third-generation regimen, in patients with low-risk aggressive lymphoma, showed that ACVBP could be beneficial for patients with more advanced disease. 11 Therefore, in 1993, the GELA initiated a phase 3 study comparing ACVBP to CHOP in patients with poor-prognosis aggressive lymphoma. We restricted this trial to patients aged between 61 and 69 years because another study from our group had shown that patients younger than 60 years of age with poor-risk aggressive lymphoma could benefit from consolidative high-dose therapy with stem cell rescue in the front-line regimen.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] Although most DLBCL respond to modern chemotherapy regimens that include an anthracycline and alkylating agents, only half of the patients are alive and disease free at 5 years. [2][3][4][5] These results make the search of potential drug resistance mechanisms particularly important in DLBCL. Widely used prognostic factors (especially those utilized for the International Prognostic Index (IPI) 6 are essentially based on the patient's general condition, disease stage, and lactico deshydrogenase (LDH) serum levels but not on specific biological abnormalities present in DLBCL tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…This regimen was compared with conventional doxorubicin, cyclophosphamide, vindesine, bleomycin, and prednisone (ACVBP), 16 which has shown benefit in event-free survival (EFS) over CHOP and methotrexate, bleomycin, cyclophosphamide, and etoposide regimens for patients with at least two adverse prognostic factors. 17,18 At the first interim analysis in September 1995, the trial was stopped because of the poor experimental arm results. 19 We report the final analysis of this trial with a median follow-up of 60 months.…”
Section: T O Improve the Cure Rate For Aggressive Non-mentioning
confidence: 99%